Public Awareness and Perception of Genetically Modified Crops: A Case Study in Wardha, Maharashtra, India (American Journal of Sustainable Agriculture and Rural Development, 2025)
This research provides an account of the awareness and perception towards GM crops: A study in Wardha, Maharashtra, India. Genetically modified (GM) crops are one of the approaches that biotechnical science has developed to meet the demand for food through higher yields and the reduction of pesticide use. On the contrary, they also evoke some biosafety and health and environmental issues It is essential to understand public attitudes especially in agricultural regions like Wardha. Method of data collection: A survey using a structured questionnaire was administered to 150 respondents selected at random in selected areas in Wardha. The questionnaire included demographics, knowledge and awareness level, sources of information, and perceptions measured using a Likert scale, complemented with open-ended questions. Data analysis involved descriptive statistics and cross-tabulation to explore relationships between demographic factors and awareness/perception. Findings reveal varying levels of awareness, often linked to education and occupation. Perception is diverse, influenced by perceived benefits and risks, often reflecting knowledge gaps and misinformation. The sources of information and demographic variables influencing attitudes are also determined in the study. Findings will contribute to developing targeted communication strategies and policy for agricultural biotechnology adoption in the region.